Platinum-Based Drugs in Cancer Therapy - Kelland, Lloyd R.; Farrell, Nicholas P. (Cancer Drug Discovery and Development, 2000)
In Platinum-Based Drugs in Cancer Therapy, leading international experts comprehensively review all aspects of platinum anticancer drugs and their current use in treatment, as well as examining their future therapeutic prospects. Writing from a variety of disciplines, these authorities discuss the chemistry of cisplatin in aqueous solution, the molecular interaction of platinum drugs with DNA, and such exciting new areas as DNA mismatch repair, replicative bypass, apoptosis, and the transport of platinum drugs into tumor cells. The antitumor activity and toxicology of platinum-based drugs is also addressed in a thorough discussion of the clinical experience with cisplatin and carboplatin, including their promising recent combinations with taxanes and oxaliplatin. The emergent platinum drugs of the future-orally active agents, the sterically hindered ZD0473, and the polynuclear charged platinum BBR3464-are also fully considered. Timely and interdisciplinary, Platinum-Based Drugs in Cancer Therapy offers cancer therapeutics specialists an illuminating survey of every aspect of platinum drugs from mechanisms of action to toxicology, tumor resistance, and new analogs. This important book captures the essence of the fresh clinical possibilities now strongly emerging thirty years after cisplatin's discovery